Engineering Saccharomyces pastorianus for the co-utilisation of xylose and cellulose from biomass. Issue 1 (December 2015) - Kricka, William; James, Tharappel; Fitzpatrick, James; Bond, Ursula
Abstract Background Lignocellulosic biomass is a viable source of renewable energy for bioethanol production. For the efficient conversion of biomass into bioethanol, it is essential that sugars from both the cellulose and hemicellulose fractions of lignocellulose be utilised. Results We describe the development of a recombinant yeast system for the fermentation of cellulose and xylose, the most abundant pentose sugar in the hemicellulose fraction of biomass. The brewer's yeastSaccharomyces pastorianus was chosen as a host as significantly higher recombinant enzyme activities are achieved, when compared to the more commonly usedS. cerevisiae . When expressed inS. pastorianus, theTrichoderma reesei xylose oxidoreductase pathway was more efficient at alcohol production from xylose than the xylose isomerase pathway. The alcohol yield was influenced by the concentration of xylose in the medium and was significantly improved by the additional expression of a gene encoding for xylulose kinase. The xylose reductase, xylitol dehydrogenase and xylulose kinase genes were co-expressed with genes encoding for the three classes ofT. reesei cellulases, namely endoglucanase (EG2), cellobiohydrolysase (CBH2) and β-glucosidase (BGL1). The initial metabolism of xylose by the engineered strains facilitated production of cellulases at fermentation temperatures. The sequential metabolism of xylose and cellulose generated an alcohol yield of 82% from the available sugars. Several different types of biomass, such as the energy cropMiscanthus sinensis and the industrial waste, brewer's spent grains, were examined as biomass sources for fermentation using the developed yeast strains. Xylose metabolism and cell growth were inhibited in fermentations carried out with acid-treated spent grain liquor, resulting in a 30% reduction in alcohol yield compared to fermentations carried out with mixed sugar substrates. Conclusions Reconstitution of complete enzymatic pathways for cellulose hydrolysis and xylose utilisation inS. pastorianus facilitates the co-fermentation of cellulose and xylose without the need for added exogenous cellulases and provides a basis for the development of a consolidated process for co-utilisation of hemicellulose and cellulose sugars.